Eksplorasi Kearifan Lokal Pande Besi di Kampung Logam Desa Ngingas Sebagai Sumber Belajar Berbasis Etnopedagogi - Arifah, Mamik; Widodo, Wahono; Istig’faroh, Nurul (Tumoutou Social Science Journal, 2024)
Abstract, The blacksmith tradition in Indonesia reflects cultural values, perseverance and skills passed down from generation to generation which not only have economic value but also educational value. The blacksmith profession utilizes hereditary skills in heating and processing metal, which are relevant to scientific concepts. This research aims to integrate the blacksmith profession in Pandean Hamlet, Ngingas Village as a learning resource on heat-conducting materials for elementary school students with a local wisdom approach through ethnopedagogy. This research aims to explore blacksmith activities as a source of ethnopedagogical learning in elementary schools. Using descriptive qualitative research methods, this research explores the processes and techniques used by blacksmiths in heating and processing metal, as well as the cultural values contained in the blacksmithing profession.  Data was collected through direct observation, in-depth interviews with blacksmiths, as well as documentation of their daily activities. The research results show that blacksmithing practices in Pandean Hamlet, Ngingas Village contain educational value that can be integrated into science material for elementary schools. The process of heating metal at a blacksmith provides a concrete example of the concept of heat conductor, where heated metal becomes a good conductor of heat and changes shape according to the heat treatment given. Black pande activities involve local values such as hard work, perseverance, and skills, which are important to teach to students in character building. The conclusion of this research is that blacksmith activities in Ngingas Village have the potential to be an effective learning resource, not only in explaining the concept of heat conduction, but also in instilling cultural values and life skills in students.